Effect of posterior corneal astigmatism on refractive outcomes after toric intraocular lens implantation. Issue 1 (January 2015) - Zhang, Lijun; Sy, Mary Ellen; Mai, Harry; Yu, Fei; Hamilton, Rex D.
Abstract : Purpose : To compare the prediction error after toric intraocular lens (IOL) (Acrysof IQ) implantation using corneal astigmatism measurements obtained with an IOLMaster automated keratometer and a Galilei dual rotating camera Scheimpflug–Placido tomographer. Setting : Jules Stein Eye Institute, University of California Los Angeles, Los Angeles, California, USA. Design : Retrospective case series. Methods : The predicted residual astigmatism after toric IOL implantation was calculated using preoperative astigmatism values from an automated keratometer and the total corneal power (TCP) determined by ray tracing through the measured anterior and posterior corneal surfaces using dual Scheimpflug–Placido tomography. The prediction error was calculated as the difference between the predicted astigmatism and the manifest astigmatism at least 1 month postoperatively. The calculations included vector analysis. Results : The study evaluated 35 eyes (35 patients). The preoperative corneal posterior astigmatism mean magnitude was 0.33 diopter (D) ± 0.16 (SD) (vector mean 0.23 × 176). Twenty‐six eyes (74.3%) had with‐the‐rule (WTR) posterior astigmatism. The postoperative manifest refractive astigmatism mean magnitude was 0.38 ± 0.18 D (vector mean 0.26 × 171). There was no statistically significant difference in the mean magnitude prediction error between the automated keratometer and TCP techniques. However, the automated keratometer method tended to overcorrect WTR astigmatism and undercorrect against‐the‐rule (ATR) astigmatism. The TCP technique lacked these biases. Conclusions : The automated keratometer and TCP methods for estimating the magnitude of corneal astigmatism gave similar results. However, the automated keratometer method tended to overcorrect WTR astigmatism and undercorrect ATR astigmatism. Financial Disclosure : Dr. Hamilton has received honoraria for educational lectures from Ziemer Ophthalmic Systems. No other author has a financial or proprietary interest in any material or method mentioned.